If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -4(w + 5) + 9 = -31 Reorder the terms: -4(5 + w) + 9 = -31 (5 * -4 + w * -4) + 9 = -31 (-20 + -4w) + 9 = -31 Reorder the terms: -20 + 9 + -4w = -31 Combine like terms: -20 + 9 = -11 -11 + -4w = -31 Solving -11 + -4w = -31 Solving for variable 'w'. Move all terms containing w to the left, all other terms to the right. Add '11' to each side of the equation. -11 + 11 + -4w = -31 + 11 Combine like terms: -11 + 11 = 0 0 + -4w = -31 + 11 -4w = -31 + 11 Combine like terms: -31 + 11 = -20 -4w = -20 Divide each side by '-4'. w = 5 Simplifying w = 5
| 5(m-5)+5=40 | | n+9=3n+5*5 | | -12x+8y=36 | | 35.84=27.02+294.9*x-373.7x | | -1(2n+3)=2(-4-7) | | 20-2(2w+1)=5w-2(5+w) | | 0*3+4=0*2+3 | | n+9=3n+5*4 | | f/7-8=72 | | 8(t+2)-3(t-4)=6(t-7) | | 6-9x=26-23x | | 2x-175=755 | | 26.6x+76.6x+200x=5513 | | 2x+11=-37-10 | | 60=12x | | 5x+4=4555 | | 8x-8y=-16 | | 2x+5x/9=-30 | | f+13=27 | | 7=q-83 | | 6n-4(n-3)=n+3 | | 3x+7=(5x-4)*2 | | 9+(2/3)x=81 | | -7c(3/4)=65 | | 6-4y=y | | 2a-3=3-4a | | 3a-6=10-a | | (2x-2)2=(3x-2)(x-3) | | 24+2x-x^2= | | 132-6x=2x-20 | | 12x-5=8x-x | | x(p-cv)=cf |